2013
DOI: 10.1002/2013jb010107
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse elastic wavefield within a simple crustal model. Some consequences for low and high frequencies

Abstract: [1] The reliability of usual assumptions regarding the wavefield composition in applications of the Diffuse Field Approach (DFA) to passive seismic prospecting is investigated. Starting from the more general formulation of the DFA for full wavefield (FW), the contribution of each wave to the horizontal-and vertical-component power spectra at surface are analyzed for a simple elastic waveguide representing the continental crust-upper mantle interface. Special attention is paid to their compositions at low and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…No strong evidence supports that the peak amplitude indicates the amplification factor of the site and there is some controversy about the nature of the ambient noise wave field and its sources (Sánchez-Sesma et al, 2011). During the past few decades, two research branches have formed to interpret the ambient noise wave field: Rayleigh wave ellipticity (Fäh et al, 2001;Wathelet et al, 2004) and the full wave-field assumptions, including distributed surface sources (DSSs, Lunedei and 798 P. Yan et al: Antarctic ice sheet thickness estimation Albarello, 2009Albarello, , 2010 and diffuse field assumption (DFA, Shapiro and Campillo, 2004;Sánchez-Sesma and Campillo, 2006;Sánchez-Sesma et al, 2011;García-Jerez et al, 2013. To calculate the H / V spectrum, a specialized GEOPSY program was developed by the European SESAME team, and widely used to investigate sediment structures (Bard and SESAME Team, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…No strong evidence supports that the peak amplitude indicates the amplification factor of the site and there is some controversy about the nature of the ambient noise wave field and its sources (Sánchez-Sesma et al, 2011). During the past few decades, two research branches have formed to interpret the ambient noise wave field: Rayleigh wave ellipticity (Fäh et al, 2001;Wathelet et al, 2004) and the full wave-field assumptions, including distributed surface sources (DSSs, Lunedei and 798 P. Yan et al: Antarctic ice sheet thickness estimation Albarello, 2009Albarello, , 2010 and diffuse field assumption (DFA, Shapiro and Campillo, 2004;Sánchez-Sesma and Campillo, 2006;Sánchez-Sesma et al, 2011;García-Jerez et al, 2013. To calculate the H / V spectrum, a specialized GEOPSY program was developed by the European SESAME team, and widely used to investigate sediment structures (Bard and SESAME Team, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…In this frame, the displacement power can be linked with the source filed power via the Green's function, which, in turn, depends on the subsoil configuration. About the DFA model, very recently García-Jerez et al (2013) have shown some consequence, at low and high frequencies, of its application to a simple crustal model. The most recent development of this model is its application to a case where a lateral variation exists, by Matsushima et al (2014).…”
Section: A Mention To the Most Recent Results In H/v Modellingmentioning
confidence: 99%
“…One possible approach is to apply Bouchon's (2007) Discrete Wavenumber Method, instead the focus of this research is to isolate the contributions of the various waves. To this end, the expressions obtained by García-Jerez et al (2013;2016) are used. The kernels in the ( , ) domain, where = horizontal (radial) component of the wave vector, are extended to the complex -plane.…”
Section: Theoretical H/vmentioning
confidence: 99%
“…As shown in García-Jerez et al (2013;2016) the expressions of the imaginary part of the Green's function, for the special case when source and receiver coincide at the top of the layered media, can be written in a very compact form. It is clear that the contributions from surface and body waves can be isolated:…”
Section: Theoretical H/vmentioning
confidence: 99%